Assessing the psychological skill of factory fire squad responding to emergency at Sungai Way Free Industrial Zone, Petaling Jaya, Malaysia - Ching, Eng Leong (2000)
Nowadays the public is more aware of the importance of the private fire squad. This study was conducted to assess the psychological skill of factory fire squad affecting the effectiveness in responding to emergency and fire fighting at factories in the Sungai Way Free Industrial Zone, Petaling Jaya and compared to The Bomba Hazmat Team (Control). The psychological skills evaluated were confidence, physical arousal, attention control, arousal control, imagery use, commitment, self-talk use and physical condition. Results show level of psychological of factory fire squad and level of psychological is different within the factory fire squads «.05); duration of experience in fire squad and academic qualification do not have significant effect on psychological skills.